1998
DOI: 10.1016/s0022-5223(98)70287-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde Autologous Priming For Cardiopulmonary Bypass: A Safe And Effective Means Of Decreasing Hemodilution And Transfusion Requirements

Abstract: These data suggest that retrograde autologous priming is a safe and effective means of significantly decreasing hemodilution and the number of patients requiring red cell transfusion during cardiac operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
97
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(104 citation statements)
references
References 24 publications
5
97
1
1
Order By: Relevance
“…The original RAP method, described by Rosengart et al [7], modified by Eising et al [10], as follows, was adopted in this investigation (Figure 1 mmHg, using small doses of intravenously administered phenylephrine. A recirculation bag was connected to the venous line.…”
Section: Methods Of the Retrograde Autologous Priming (Rap)mentioning
confidence: 99%
See 1 more Smart Citation
“…The original RAP method, described by Rosengart et al [7], modified by Eising et al [10], as follows, was adopted in this investigation (Figure 1 mmHg, using small doses of intravenously administered phenylephrine. A recirculation bag was connected to the venous line.…”
Section: Methods Of the Retrograde Autologous Priming (Rap)mentioning
confidence: 99%
“…Retrograde autologous priming (RAP) is a method of CPB, at low cost, which has been described [1,7] as modification of the method proposed, in 1959, by Panico and Neptune [8]. Previous studies have shown that this method reduces hemodilution during CPB, the reduction of blood transfusions by increasing the hematocrit intraoperatively, especially in patients who have risk factors as anemia, small body surface area, and refuses to receive blood products [1].…”
Section: Introductionmentioning
confidence: 99%
“…Starting preoperatively by raising the level of hemoglobin by use of EPO and iron therapy, eliminating any hemodilution, to proper operative field drainage to reduce the incidence of hematomas related to various invasive maneuvers over the course of hospitalization, keeping the hemoglobin value under 15.5 to avoid associated complications with high hematocrit value [16]. The most recent example of this comprehensive multimodality approach is the mini-cardiopulmonary bypass system that we have been using for the last three years, combined with retro-priming and a cell saver [16][17][18][19][20][21] which maintains a constant hemoglobin level, often low in cardiac patients. Volume expansion in these patients is associated with a real risk of hemodilution and active participation of the anesthetist is essential to avoid additional iatrogenic vasoplegia, which is greatly facilitated by concentration-aimed ultra-fasttrack anesthesia protocols [22].…”
Section: ) Transfusion Pro and Conmentioning
confidence: 99%
“…During this drainage, the bloodless prime is redirected to a separate reservoir. This is a well established way to decrease autologous blood transfusion in adult cardiac surgery [67,68] . This strategy is very uncommon in pediatric cardiac surgery, but it could be part of a bloodless surgical program [69] .…”
Section: Maneuver Of Retrograde Autologous Primingmentioning
confidence: 99%